Bankruptcy Prediction in PT Blue Bird, Tbk 2011-2016 Using Altman Z-Score, Springate, and Zmijewski Model - Fian Metal Angga Pertapan, Sri Hartono & Ida Aryati Dyah Purnomo Wulan (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
The aim of this study is to determine the financial condition of PT. Blue Bird, Tbkin 2011-2016 by using Altman Z-score, Springate, and Zmijewski model, inpurpose to predict the financial distress that occurs in the company. The data usedin this study are the secondary data from Transportasi Service Companies, namelyPT. Blue Bird, Tbk. Data analysis techniques of this study are the discriminantanalysis of Altman, Springate, and Zmijewski. The analysis of Altman model isgrouped into three parts of companies, include companies that experience goodcondition, grey areas, and bankruptcy. Springate model analysis is grouped intotwo parts of companies, include companies that is in good condition and potentiallybankrupt. The analysis of Zmijewski model is grouped into two parts of companies,include companies that are good condition and potentially bankrupt. The results offinancial distress analysis of PT. Blue Bird, Tbk period 2011-2016 using Altmanmodel indicates that companies in the category grey areas. The results of theanalysis using Springate model shows that companies in the category goodcondition. The analysis result using Zmijewski model also shows companies in thecategory good condition.Keywords: Altman, Bankruptcy, Springate, Zmijewski